2021
DOI: 10.3389/fvets.2021.601394
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Feeding Antibiotic on the Intestinal Microbiota of Weanling Pigs

Abstract: This study investigated the use of carbadox in the diet of nursery pigs. Ten pens of weanling piglets were assigned to 2 treatments: one containing carbadox and another without it. From days 21 to 35 of age, the first group of piglets was fed carbadox at 55 mg/kg of diet; followed by 27.5 mg/kg from days 36 to 49; and 0 mg/kg from days 50 to 63. The second group of pigs was fed a control diet without carbadox from days 21 to 63 of age. On days 35, 49, and 63, fecal samples were collected directly from the rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…The relative abundance of Bacteroidetes was also numerically higher in carbadox group than pigs in control. These observations indicate the impacts of in-feed antibiotics on gut microbiome were immediate (Lourenco et al, 2021). The reduced Lactobacillaceae in feces is consistent with previous research (Gao et al, 2018), suggesting that supplementation of carbadox modified the intestinal environment…”
Section: Fecal Microbiotasupporting
confidence: 89%
“…The relative abundance of Bacteroidetes was also numerically higher in carbadox group than pigs in control. These observations indicate the impacts of in-feed antibiotics on gut microbiome were immediate (Lourenco et al, 2021). The reduced Lactobacillaceae in feces is consistent with previous research (Gao et al, 2018), suggesting that supplementation of carbadox modified the intestinal environment…”
Section: Fecal Microbiotasupporting
confidence: 89%
“…Metabolic pathways, such as genetic information processing and human diseases, were significantly enriched in the MPR. Studies have shown that antibiotics can substantially increase the expression of the genetic information processing genes of gut microbes in humans (Francino, 2016) and piglets (Lourenco et al, 2021). These findings are consistent with those of our study, indicating that antibiotic residues can affect the function of plateau pika intestinal flora through horizontal transmission.…”
Section: Figuresupporting
confidence: 93%
“…Weaning stress had negative effects on antioxidant capacity, immunity, intestinal morphology and growth performance [ 1 , 2 , 3 ]. Formerly, antibiotics were widely used to alleviate weaning stress [ 4 ]. However, the ban of antibiotic use in feed worldwide forces researchers to find antibiotic alternatives.…”
Section: Introductionmentioning
confidence: 99%